Improving Employment Prospects for Young Workers in Spain - Wölfl, Anita (OECD Publishing, 2013)
The unemployment rate among young people has reached painfully high levels, in particular among those young people with low levels of education. There are two crucial policy priorities to improve employment prospects for youth in Spain. First, in the very short term, there is need for quick action to target welldesigned active labour market programmes to the most disadvantaged youth and provide more job-search assistance and guidance for all youth experiencing difficulties in finding a job in the current labour market. Second, the current crisis is an opportunity to tackle some of the structural weaknesses in the Spanish youth labour market. This implies in particular reforms to prevent youth from dropping out of education at a very early stage and to improve the school to work transition of young people. Key issues are to better match skills acquired in education to those asked for by businesses, as well as to establish an effective system of vocational education, and to reduce remaining demand side barriers, notably labour market duality and a rigid collective bargaining system, which both have prevented an efficient allocation of labour resources in the past and a flexible adjustment during the crisis. This Working Paper relates to the 2012 OECD Economic Survey of Spain (www.oecd.org/eco/surveys/spain)
Keywords: Employment; Economics; Spain